2016
DOI: 10.1128/jvi.03206-15
|View full text |Cite
|
Sign up to set email alerts
|

Range of CD4-Bound Conformations of HIV-1 gp120, as Defined Using Conditional CD4-Induced Antibodies

Abstract: The HIV envelope binds cellular CD4 and undergoes a range of conformational changes that lead to membrane fusion and delivery of the viral nucleocapsid into the cellular cytoplasm. This binding to CD4 reveals cryptic and highly conserved epitopes, the molecular nature of which is still not fully understood. The atomic structures of CD4 complexed with gp120 core molecules (a form of gp120 in which the V1, V2, and V3 loops and N and C termini have been truncated) have indicated that a hallmark feature of the CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…Then, the chemokine receptors bind to the bridging sheet region on gp120 and the entry step follows the membrane fusion through gp41 [ 6 9 ]. The bridging sheet consists of a four-stranded β-sheet structure composed of two double-strand β-sheet structures, hairpin 1 (H1 containing β2 and β3 in the stem of the V1/V2 loops) and hairpin 2 (H2 containing β20 and β21 in the C4 region) [ 5 , 10 ]. These β-sheets are highly conserved among HIV-1 strains because the structure and amino acid sequences are critical for the interaction with the N-terminus of CCR5, suggesting it is the main component of the co-receptor binding site [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the chemokine receptors bind to the bridging sheet region on gp120 and the entry step follows the membrane fusion through gp41 [ 6 9 ]. The bridging sheet consists of a four-stranded β-sheet structure composed of two double-strand β-sheet structures, hairpin 1 (H1 containing β2 and β3 in the stem of the V1/V2 loops) and hairpin 2 (H2 containing β20 and β21 in the C4 region) [ 5 , 10 ]. These β-sheets are highly conserved among HIV-1 strains because the structure and amino acid sequences are critical for the interaction with the N-terminus of CCR5, suggesting it is the main component of the co-receptor binding site [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subtle difference in their reacting epitopes may account for the difference in neutralization potency among anti-CD4i scFvs. Analysis using a series of Env mutants revealed that individual anti-CD4i mAbs had various dependencies for the H1, V1/V2 loops and V3 stem regions [ 10 , 18 ]. In addition, the binding of CD4 significantly affected the dependency on these regions [ 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because V4 and V5 are connected to b20 (one of bridging-sheet elements) and a5 (layer 3) through rigid b19 and b24, respectively, it is very likely that dynamical behaviours of these two surface loops may mediate/modulate conformational dynamics of the b20-b21 hairpin and layer 3, respectively. The stronger mobility of V4 and V5 in R2-gp120 likely makes a larger contribution to increasing uctuations of b20-b21 and a5, respectively, which have been shown important for triggering the formation of bridging sheet 16,58,59 and for communication between inner and outer domains, 15,16 respectively.…”
Section: Conformational Exibilitymentioning
confidence: 99%
“…6E) will enlarge the cavity located between the inner and outer domains, allowing b20-b21 hairpin to move in the same direction as layers 1 and 2. Previous studies 37,40,58 have suggested that the opening of inter-domain cavity followed by the rearrangement of b20-b21 hairpin is a crucial initial step for triggering gp120's conformational transition from the unliganded to the CD4bound state since the reorientation of b20-b21 results in the formation of the mature CD4-Phe43-binding pocket and the disruption of hydrogen bonds between b3 and b21, which is a prerequisite for further repositioning of V1/V2 and the formation of the mature bridge sheet. In the motional mode along the eigenvector 3 ( Fig.…”
Section: Collective Motionsmentioning
confidence: 99%
See 1 more Smart Citation